Fatores intervenientes e variações nos limiares auditivos em população pediátrica no período pós-diagnóstico - Ogeda, Elaine Cristina Moreira (2014)
The early detection and diagnosis of hearing loss enable for appropriate intervention, providing the conditions for the child's development of speech, language, hearing, and of psychosocial and educational aspects. However, the diagnostic process can be considered complete only when specifically identified the type, degree and configuration of hearing loss these children. The hearing evaluation process is very important and at the same time dynamic. In this direction, to analyze possible variations in hearing thresholds and consequent changes in the values used for prescription procedures in hearing aids programming are necessary when establishing protocol issues to be addressed when it comes to the pediatric population. Objective: To identify factors that can lead to variations of auditory thresholds in children in the post-diagnosis period. Method: In the period studied were analyzed medical and audiological records of 66 subjects who were diagnosed with hearing loss, selection and fitting of hearing aids performed in CeAC. A hearing descriptive analysis of the subject was performed in the diagnostic process to the fitting of hearing aids. Changes in hearing threshold over the period were analyzed considering factors involved in each return appointment. Results and Discussion: The results show that of the 66 subjects for analysis, 18 (27.3 %) were eliminated because they had only one threshold of diagnostic and they did not perform the monitoring period. 62% subjects were male, 38% female, with a mean chronological age at diagnosis of 23 months, the newest initiated the treatment with 1 month of age and the oldest with 80 months. These subjects, just 2% were classified with mild hearing loss, 17% had moderate degree of hearing loss, 33% had severe degree of hearing loss and 48% had profound degree of hearing loss. 29% of the total sample showed variation in the degree of hearing loss, and 35% of these symmetric hearing losses and 54% asymmetric. In the hearing losses asymmetric when the auditory thresholds in the diagnostic and the last period studied, 28 subjects (58.3%) had improvement or worsening compared the initial thresholds. The factors identified as responsible for variations were neural maturation, progression of hearing loss and presence of otitis. Conclusion: Over the past 10 years, it has been observed that newborn hearing screening programs in hospitals has enabled the diagnosis of hearing impairment earlier in life. Considering the differences in hearing thresholds found over time in children who underwent ABR-FE in the first six months of life, this exam has been effective in determining the hearing thresholds in the period in which VRA is not yet possible. The variation of hearing thresholds related to maturation, progression and otitis suggests that regular monitoring of children diagnosed early in life should be done as systematic procedure at intervals of three to four months, considering the maturity period and the difficulty of parental observation of behaviors related to possible variations in the hearing thresholds